Age-related differences of oncological outcomes in primary extremity soft tissue sarcoma: a multistate model including 6260 patients. (December 2020) - Acem, Ibtissam; Verhoef, Cornelis; Rueten-Budde, Anja J.; Grünhagen, Dirk J.; van Houdt, Winan J.; van de Sande, Michiel A.J.; ,; Aston, Will; Bonenkamp, Han; Desar, Ingrid M.E.; Ferguson, Peter C.; Fiocco, Marta; et al.
Abstract: Purpose: No studies extensively compared the young adults (YA, 18–39 years), middle-aged (40–69 years), and elderly (≥70 years) population with primary high-grade extremity soft tissue sarcoma (eSTS). This study aimed to determine whether the known effect of age on overall survival (OS) and disease progression can be explained by differences in tumour characteristics and treatment protocol among the YA, middle-aged and elderly population in patients with primary high-grade eSTS treated with curative intent. Methods: In this retrospective multicentre study, inclusion criteria were patients with primary high-grade eSTS of 18 years and older, surgically treated with curative intent between 2000 and 2016. Cox proportional hazard models and a multistate model were used to determine the association of age on OS and disease progression. Results: A total of 6260 patients were included in this study. YA presented more often after 'whoops'-surgery or for reresection due to residual disease, and with more deep-seated tumours. Elderly patients presented more often with grade III and larger (≥10 cm) tumours. After adjustment for the imbalance in tumour and treatment characteristics the hazard ratio for OS of the middle-aged population is 1.46 (95% confidence interval [CI]: 1.22–1.74) and 3.06 (95% CI: 2.53–3.69) in the elderly population, compared with YA. Discussion: The effect of age on OS could only partially be explained by the imbalance in the tumour characteristics and treatment variables. The threefold higher risk of elderly could, at least partially, be explained by a higher other-cause mortality. The results might also be explained by a different tumour behaviour or suboptimal treatment in elderly compared with the younger population. Highlights: Young adults presented more often after 'whoops'-surgery or reresection. Elderly patients presented more often with grade III and larger tumours. With increasing age, overall survival decreases and recurrence rates increases. This could partially be explained by the imbalance in tumour/treatment variables.